Medullary Thyroid Cancer Follow-Up Results: 20 Years of Experience in a Tertiary Center - Kara, Zehra; Demir, Ahmet Numan; Sulu, Cem; Gönen, Mustafa Sait (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of our study was to present our experience with medullary thyroid cancer and to identify the characteristics of patients in relapse or remission. Methods: In this study, data from medullary thyroid cancer (MTC) patients followed at Istanbul University Cerrahpasa, Cerrahpasa Medical Faculty, Endocrinology and Metabolism outpatient clinic.. Electronic records and files of patients older than 18 years of age between January 2000 and June 2022 were retrospectively reviewed. Patients with medullary thyroid cancer were selected from patients with thyroid malignancy. Patient information was obtained from files. Results: A total of 855 thyroid cancer patient files were reviewed. Medullary thyroid cancer accounted for 3.5% of all thyroid cancers. A total of 30 patients with medullary thyroid cancer [median (interquartile range): age, 45 (34–59) years; 17 female (56.7%)] were included in the analysis. Data were analyzed with a median follow-up of 60 (24–120) months. The median tumor size was 15 mm (8-30), and 20% of patients had multifocal and/ or bilateral tumors. While 40% of the patients had N1 disease, 30% of the patients had distant metastases and 30% of patients had clinical stage 4C, according to The American Joint Committee on Cancer, 8th edition. Another aim is to try to identify the characteristics of patients at risk of disease recurrence or non-remission were examined, more extrathyroidal spread (P = .01), larger tumor size (P = .003), and more lymph node metastases (P < .001) and distant metastases (P < .001) were observed, and postoperative third-month calcitonin and carcinoembryonic antigen levels were higher (P = .01, for all). In the survival analysis, at 25th and 80th months, we found that survival decreased despite chemotherapy (P = .017 and .002, respectively) and radiotherapy (P = .002 and <.001, respectively) treatment. Calcitonin and carcinoembryonic antigen cut-off values predicting relapse in medullary thyroid cancer were determined to be 5.3 pg/mL and 8.6 ng/mL, respectively. Conclusion: Medullary thyroid cancer is a rare cancer and has a good prognosis when detected at an early stage. In cases of advanced or metastatic disease, the prognosis is poor despite treatment. Calcitonin and carcinoembryonic antigen levels measured at postoperative third month can be used to predict recurrence. Cite this article as: Kara Z, Demir AN, Sulu C, Gönen MS. Medullary thyroid cancer follow-up results: 20 years of experience in a tertiary center. Cerrahpaşa Med J. 2023.